Review Artikel : Potensi Actinomycetes Sebagai Antijamur Pada Suatu Tanaman - Oktavianti, Alfina; Salsabilla, Isyana (JURNAL PERTANIAN, 2024)
Plant damage caused by phytopathogenic fungi is a serious issue in agriculture. Conventional approaches using synthetic pesticides have proven effective in controlling plant diseases but pose environmental and health problems and increase pathogen resistance to chemicals. Consequently, recent research focuses on developing environmentally friendly and effective biocontrol agents. Numerous studies highlight the potential use of microbial-based biocontrol agents, such as bacteria and fungi from the genera Streptomyces, Bacillus, and Pseudomonas, in protecting plants from diseases. Specifically, actinomycetes, a subgroup of bacteria that produce bioactive secondary metabolites, have been successfully utilized as biocontrol agents against phytopathogenic fungi and bacteria. This study employs a literature review method, searching through Google Scholar and PubMed with keywords such as Antifungal Activity, Actinomycetes, Phytopathogens, and Plant Biocontrol Agents. The results indicate that actinomycetes are widely used as antifungal agents in agriculture, possessing various antagonistic mechanisms against phytopathogenic fungi through secondary metabolites, host resistance induction, siderophores, and lytic enzymes. This review article examines the various mechanisms of actinomycetes as biocontrol agents in agriculture and their antagonistic roles against phytopathogenic fungi, presenting an alternative to the future use of synthetic fungicides